A generic approach to detect design patterns in model transformations using a string-matching algorithm - Mokaddem, Chihab eddine; Sahraoui, Houari; Syriani, Eugene (Software and systems modeling, 2022)
Maintaining software artifacts is a complex and time-consuming task. Like any other program, model transformations are subject to maintenance. In a maintenance process, much effort is dedicated to the comprehension of programs. To this end, several techniques are used, such as feature location and design pattern detection. In the particular case of model transformations, detecting design patterns contributes to a better comprehension as they carry valuable information on the transformation structure. In this paper, we propose a generic approach to detect, semi-automatically, design patterns and their variations in model transformations. Our approach encodes both design patterns and transformations as strings and use a string-matching algorithm for the detection. The approach is able to detect complete and partial implementations of design patterns in transformations, which is useful to refactoring and improving model transformations.